Pyridazine and pyridazinone derivatives as potent and selective factor XIa inhibitors. Issue 6 (1st April 2018) - Hu, Zilun; Wang, Cailan; Han, Wei; Rossi, Karen A.; Bozarth, Jeffrey M.; Wu, Yiming; Sheriff, Steven; Myers, Joseph E.; Luettgen, Joseph M.; Seiffert, Dietmar A.; Wexler, Ruth R.; Quan, Mimi L.
Graphical abstract: Abstract: Pyridazine and pyridazinone derivatives were designed and synthesized as coagulation factor XIa inhibitors. Potent and selective inhibitors with single digit nanomolar affinity for factor XIa were discovered. Selected inhibitors demonstrated moderate oral bioavailability.